PENERAPAN MODEL POE (PREDICT, OBSERVE, EXPLAIN) BERBANTUAN MEDIA CANVA UNTUK MENINGKATKAN HASIL BELAJAR MURID MATERI GAYA KELAS IV SEKOLAH DASAR - Amelia Burhan; Meylan Saleh; Rifda Mardian Arif; Kudus; Gamar Abdullah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low learning outcomes of fourth-grade students on the topic of force at SDN 5 Tilongkabila. Several problems were identified, including the limited variation in instructional models, which resulted in low student participation during the learning process, inadequate learning media, the failure of most students to meet the learning achievement criteria, and differences in students’ academic abilities that required a more systematic and interactive learning approach. The research problem addressed in this study was whether the implementation of the Predict, Observe, Explain (POE) learning model assisted by interactive Canva media could improve students’ learning outcomes on the topic of force in Grade IV at SDN 5 Tilongkabila. This study aimed to describe the improvement in students’ learning outcomes through the implementation of the POE learning model supported by interactive Canva media. The study employed Classroom Action Research (CAR) conducted in two cycles, consisting of planning, action implementation, observation, evaluation, and reflection stages. The research subjects were 13 students, comprising 5 male students and 8 female students. The preliminary observation revealed that only 5 students (38.46%) achieved mastery learning. In Cycle I, the number of students achieving mastery increased to 9 students (69.23%), although it had not yet reached the success indicator of 80%. In Cycle II, students’ learning outcomes further improved, with 11 students (84.62%) achieving mastery learning. Therefore, the implementation of the POE learning model assisted by interactive Canva media was proven to improve students’ learning outcomes on the topic of force in Grade IV at SDN 5 Tilongkabila.